2015
DOI: 10.3947/ic.2015.47.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence of Mumps in Korea

Abstract: Routine vaccination against mumps has markedly reduced its incidence. However, the incidence of mumps continuously has increased since 2007. In 2013, a large mumps epidemic occurred in Korea, and this epidemic is still an ongoing problem. This epidemic occurred primarily in school settings and affected vaccinated adolescents, predominantly male students. The recent resurgence of mumps is caused by multiple factors: suboptimal effectiveness of the current mumps vaccines, use of the Rubini strain vaccine, waning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 52 publications
1
53
0
2
Order By: Relevance
“…Mumps was a serious disease that cause significant morbidity and mortality worldwide before the program of mumps vaccination starting [5]. In the pre-vaccine era, mumps was a severe contagious disease with a high morbidity of approximately 40-726 cases per 100,000 population per year [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] ( Table 1). During the pre-vaccine era, mumps was circulating endemically with a periodic spike of two to five years and a peak incidence of infection among children aged five to seven years old in several regions globally [23][24][25][26].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Mumps was a serious disease that cause significant morbidity and mortality worldwide before the program of mumps vaccination starting [5]. In the pre-vaccine era, mumps was a severe contagious disease with a high morbidity of approximately 40-726 cases per 100,000 population per year [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] ( Table 1). During the pre-vaccine era, mumps was circulating endemically with a periodic spike of two to five years and a peak incidence of infection among children aged five to seven years old in several regions globally [23][24][25][26].…”
Section: Epidemiologymentioning
confidence: 99%
“…Incidence of MuV infection among vaccinated school-and high school-age children increased in the late 1980s, followed by sustained decrease in incidence after children were recommended to receive a second dose of MMR vaccine at four six years of age [41]. However, resurgence of outbreaks of MuV infection continues to occur in developed countries in recent years [7,18,29]. Based on the previous studies [77,83,85], the vaccine has proven itself to be highly efficacious.…”
Section: Emerging Mumps Virus Infectionmentioning
confidence: 99%
“…The seasonable distribution of mumps has been detected in various areas, with the highest incidence occurring in spring (Park, 2015;Sane et al, 2014;Shah et al, 2006). However, the seasonal distribution varies between northern and southern China, with the peaks in spring and summer respectively (Li et al, 2017b;Liu et al, 2015;Yang et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that this decrease may contribute to some of the recent outbreaks. It has been shown that there is variation in serum neutralizing antibodies among people over time [21,4143]. Poor immune responses or waning immunity may result in some individuals dropping below a protective threshold.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, where the Jeryl Lynn (genotype A) and Urabe AM9 (genotype B) strains are used for vaccination, the most common circulating MuV are genotype H [21]. The genotype C virus circulating in India may not be neutralized effectively after immunization with their L-Zagreb vaccine (genotype N) [22].…”
Section: Introductionmentioning
confidence: 99%